Clssification of flow standards of carbonate formation in Bereketli-Pirgui gas field. (October 2019) - Xing, Yuzhong; Guo, Chunqiu; Cheng, Muwei; Chen, Pengyu; Shi, Haidong; Yang, Huiting
Abstract: Callovian-Oxfordian carbonate formation in Bereketli-Pirgui gas field as an example was selected. This paper describes three methods for quantitative division of flow standards based on parameters such as pore throat size, FZI's(Flow Zone Index), storage capacity, and flow capacity. In this connection, the results can not only reflect the meter-scale heterogeneity of reservoirs around wellbore, but also meet the requirements of the minimum number of flow standards in reservoir numerical simulations. Based on the measured data of core porosity and core permeability of Callovian-Oxfordian formation, rock types are firstly identified, then the main flow standards are determined according to the FZI, and finally the main hydraulic flow standards are divided in the stratigraphic framework according to the storage capacity and flow capacity. In comparison with the single factor flow standard classification method, this method can not only realize the classification of flow standards of different scales, but also help to compare different flow standards with each other in the sequence of stratigraphic framework. The result indicates that Callovian-Oxfordian formation has 5 main rock types (i.e. micritic limestones, bioclastic microcrystalline limestones, sparry bioclastic limestones and algal limestones), 8 different flow standards (i.e. FU1-FU8) and 4 hydraulic flow standards (i.e., flow channel, storage-flow unit, storage unit and barrier unit). The classification results with different methods have a good agreement.